The effect of telemedicine on secondary prevention of atherosclerotic cardiovascular disease: A systematic review and meta-analysis - Deng, Liangying; Wu, Qing; Ding, Feng; Liu, Yanfeng; Shen, Jianping; Lin, Yan; Shi, Kaihu; Zeng, Bailin; Wu, Lixing; Tong, Huangjin (Frontiers in Cardiovascular Medicine, 2022)
Aim: The purpose of this systematic review was to evaluate the efficiency of telemedicine in the secondary prevention of patients with arteriosclerotic cardiovascular disease (ASCVD), provide evidence for the application of telemedicine in secondary prevention, and promote the development of telemedicine in secondary prevention.Method: A computer-based search was conducted in MEDLINE, Embase, Pubmed, EBSCO, CINAHL, the Cochrane Library, and Web of Science. Randomized controlled trials regarding the effect of telemedicine on secondary prevention of ASCVD were included from inception to May 2022 . Meta-analysis was used to compare the results of the included studies by RevMan5.4 soſtware. The Cochrane Collaboration bias risk tool was used to perform a risk of bias assessment in this study. Outcomes included risk factors, physical activity, and exercise, muscle function, exercise compliance, medication adherence, healthy diet, depression and anxiety, self-efficacy, knowledge score, economy, and safety endpoints. Subgroup analysis was carried out for different main intervention measures included in the literature. Results: A total of 32 randomized clinical studies (n =10 997 participants) were included in the meta-analysis. Compared with usual secondary prevention group, participants in telemedicine of secondary prevention group showed significant improvement in some risk factors including BMI (MD -0.87, p= 0.002), SBP(MD –4.09, p= 0.007), and DBP (MD -2.91, p= 0.0002) when they use the telephone as the intervention. In physical activity and exercise, Patients in TOSP showed a improvement in VO2 Peak (mL•kg−1•min−1) (OR 1.58, p= 0.02), 6MWT (MD 21.41, p=0.001), GSLTPA score (MD 2.89, p=0.005). Effects on medication adherence, exercise compliance, muscle function, healthy diet, economy, and self-efficacy were synthesized narratively. Patients in TOSP did not show a reduction in knowledge score, depression, anxiety, and safety endpoints. Conclusions: There is a net benefit of secondary prevention supported by telemedicine (especially when using the telephone as an intervention) in patients with ASCVD in the terms of some risk factors, physical activity, and exercise. There are still controversies in the improvement of medication adherence, exercise compliance, muscle function, healthy diet, knowledge score, self-efficacy, and economy via telemedicine, which is worth exploring. Larger samples size and longer-term follow-ups are needed in future studies.